Interventions to improve reading speed and fluency in Spanish speakers in Kindergarten and Primary Education: a meta-analysis - Cruz Ripoll Salceda, Juan; Zevallos Polo, Diana Sofía (Revista de Investigación en Logopedia, 2024)
There is a notable relationship between fluency and reading comprehension. To develop fluency, resources such as extensive reading and assisted reading have been used, especially repeated reading interventions. There is no systematic review or meta-analysis available regarding intervention in reading speed or fluency in Spanish-speaking students. To solve this situation, a systematic search located 16 independent effects obtained with different interventions on reading speed or reading fluency, understood as a combination of speed and accuracy or speed and prosody. Students from Kindergarten to 6th grade of Primary Education participated in these studies. The summary effect was 0.47 at the conclusion of the interventions.The results were remarkably heterogeneous. Small or moderate positive effects were found in interventions with components such as improving naming speed, oral language, decoding, reading speed, vocabulary or comprehension strategies. The results were significantly higher in interventions that included phonological awareness training and those that did not work on comprehension. The prediction intervals were positive only in interventions that did not include phonological awareness training, in which improving speed was worked explicitly, and in those that worked on comprehension: vocabulary or strategies.
Keywords: Preschool; elementary school; reading fluency; meta analysis; reading rate